Energy literacy: Evaluating knowledge, affect, and behavior of students in Taiwan - Lee, Lung-Sheng; Lee, Yi-Fang; Altschuld, James W.; Pan, Ying-Ju (Energy Policy, 2015)
Energy literacy that can empower people to make thoughtful decisions and take responsible actions is more important as energy shortages have become pressing issues in the world. Energy literacy was measured among a sample of 2400 secondary students involved in a national energy education program in Taiwan. Response patterns related to student background and factors determining energy consumption behaviors were also studied. Energy literacy was high and positive, with greater impact as expected by grade (senior high school students outscored junior high school ones) and there were some effects due to gender and socioeconomic status. Students' performance on energy knowledge was acceptable (over 60% correct across grades) while a notable discrepancy between affect and behavior was identified indicating that there might not be a correspondence between what people say they would do and what they actually do. Energy saving behavior was more closely associated with the affect than other variables. Reasons for the findings and implications for energy education in the future are discussed.
Keywords: Energy education; Energy literacy; Energy program performance